The Effect of Attractiveness of Virtual Influencer Towards the Consumer Attitudes in Developing Intention to Purchase – A Case Study of Fast Food Restaurant - Hillary Pranata Putra (Eduvest - Journal of Universal Studies, 2025)
Arbie SEO’s performance has marked an astonishing success in the Richeese Factory promotional campaign. However, despite high engagement on social media, most audience interactions and attention focus solely on Arbie SEO rather than the promoted products or the brand, which raises concerns about the actual impact of virtual influencers in developing consumer purchase intention. This study explores the effect of virtual influencer attractiveness on consumer attitudes and purchase intention, using Arbie SEO as a case study. A quantitative method was employed through a structured questionnaire targeting Gen Z respondents located in Jabodetabek and Bandung. The collected data were further processed using the SEM-PLS method. The findings of this study show that the virtual influencer’s attractiveness (Arbie SEO) has a significant and positive impact on purchase intention both directly and indirectly. Consumer attitudes play a mediating role in the attractiveness aspect in triggering consumer purchase intention. In the case of Arbie SEO, its attractiveness has been proven to have a direct effect on purchase intention, whereas most previous studies state that attractiveness alone does not have a direct effect on purchase intention. Furthermore, this research offers strategic business recommendations for utilizing the high engagement of Arbie SEO to translate attention into actual purchasing actions.